Evaluating the impact of free private well testing outreach on participants' private well stewardship in New Jersey. (19th November 2021) - Seliga, Alecia; Spayd, Steven E.; Procopio, Nicholas A.; Flanagan, Sara V.; Gleason, Jessie A.
Abstract: Over 1 million people in New Jersey (NJ) are estimated to receive drinking water from private wells. The most commonly detected contaminants in NJ private well water are naturally occurring arsenic and gross alpha (8.3 and 10.9%, respectively). Between 2015 and 2018, three free and voluntary private well testing events tested a total of 571 at-risk wells and 226 (40%) were identified as having one or more contaminants exceeding drinking water standards. Participants were invited to complete a survey to evaluate household characteristics, participant experience, and private well stewardship behavior patterns. Of 529 delivered surveys, 211 (40%) participants completed surveys. Among respondents, 63% reported plans to test their private wells in the future. Among failed wells, 45% of households reported performing mitigative action in response to the event, either through the installation of water treatment system or switching to bottled water. The survey evaluation identified previous knowledge of well contamination risks and discussing test results with a third party as important factors for promoting self-reported stewardship behavior. The evaluation provides guidance for outreach organizers to develop effective testing events and further considers the private well owners' experience of the outreach events to identify information for 'best practices' and improvements of future programs. HIGHLIGHTS: Less than half of participants report plans to perform mitigative action in response to exceeding contamination levels. This evaluation provides feedback and information which can be used to improve future voluntary private well outreach events. In addition, this study is one of the few to consider participants' experience toward free private well testing events.